Functional and Aesthetic Reconstruction for Microtia Using the Combination of Superficial Circumflex Iliac Artery Perforator Superthin Flap Transfer and Skin Grafting. Issue 7 (July 2019) - Karakawa, Ryo; Iida, Takuya; Yoshimatsu, Hidehiko; Kanayama, Koji; Yamasoba, Tatsuya
Abstract : Summary: Microtia with congenital aural atresia is challenging to achieve aesthetically and functionally good results. We herein present a case where a vascularized superthin superficial circumflex iliac artery perforator (SCIP) flap was used for reconstruction of the external auditory canal (EAC) and a full-thickness skin graft was used for reconstruction of the postauricular region for a 10-year-old male who suffered from microtia with congenital aural atresia. After costal cartilage grafting (the first operation), EAC reconstruction and auricle elevation (the second surgery) was performed. After the atticoantrostomy, a superthin SCIP flap was rolled up in a sac and was inset to the newly created EAC. The postauricular skin defect was covered with full-thickness skin graft. The SCIP flap survived completely and good patency of the reconstructed EAC was accomplished, which results in an improvement of previous hearing loss. The skin graft survived completely, which eventually demonstrated aesthetically satisfactory results.